EVALUASI PENGETAHUAN FAKTOR RESIKO DIABETES DAN DAMPAKNYA TERHADAP KADAR GULA DARAH SEWAKTU PADA MASYARAKAT KEMBANGAN UTARA, JAKARTA BARAT - Reinaldo Pradana; Melisa Resmiati; Lanny Indah Permatasari; Nadiya Nurul Afifah (Jurnal Abdi Insani, 2024)
Diabetes Mellitus (DM) is a chronic, non-communicable metabolic disease with increasing prevalence and morbidity rates. There has been a 2% increase in DM prevalence among the population aged 15 years and older, with the highest prevalence found in DKI Jakarta (2.3%). Patients' understanding or knowledge of DM and its risk factors is closely related to the incidence of type II DM. The influence of education on public knowledge and the incidence of type II DM has also been widely demonstrated. This study was conducted to map the profile of Random Blood Glucose (RBG) levels and the knowledge of the residents of Kelurahan Kembangan Utara, West Jakarta, regarding the risk factors for type II DM and preventive measures. Methods: Community education was carried out through a mini-seminar on type II DM risk factors and prevention, followed by a questionnaire to assess knowledge, RBG testing, and consultation on the interpretation of the results, as well as the distribution of educational pamphlets as visual aids. Results and Conclusion: Respondents' knowledge about good nutrition as a preventive measure for type II DM was found to be lacking. However, their knowledge of type II DM risk factors and RBG levels was considered fairly good (75 and 112 mg/dL). The study also showed no significant differences in RBG levels among respondents with questionnaire scores of 60, 80, and 100 (p≥0.05), although the median RBG level in the 60-score group was the highest. Clinically, this could be interpreted to suggest that respondents with the lowest scores had the highest RBG levels.